Bibliometric study of the combustion of cane cutting waste (RAC) in the capture of carbon dioxide - Sandra E. Peña; Carmen R. Forero; Francisco J. Velasco (SN Applied Sciences, 2022)
Abstract The bibliometric observational study in this research describes the search carried out by the authors, the statistical and regular behavior for a period of five years, focusing on the different elements related to the combustion process of the RAC of sugar cane with CO2 capture by manganese-based oxygen carriers during the 2015–2020 period. Main measurements: In each record, journal, year of publication, first/last author, work center and autonomous community were obtained, related to the investigation of combustion of cutting waste in the capture of CO2 by means of manganese-based oxygen carriers. The information was classified and later the articles were classified according to their content or research area. The impact factor was obtained from Scopus and Vosviewer bibliometric analyses.Using the search criteria used, 475 documents were retrieved in the 2015–2020 five-year period, excluding 2637 because they did not correspond to affiliation with centers or institutions directly related to documents related to Chemical combustion and CO2 capture. In total, 73 documents were selected, in which an increase and interest in the study of these processes was verified both in the research areas and in the journals in which they are published. Most of the studies have been published in universities or research centers and differences were observed in terms of the volume of international and national scientific production, being necessary to increase these investigations in the country of Colombia.